Fluid/Thermal/Structural Coupling Simulation on Effects of Forebody-Inlet Thermal Deformation on Intake Performance - Si-yi LI; Lei LIU; Xiao-feng YANG; Zi-yi WANG; Yan-xia DU; Ye-wei GUI (气体物理, 2023)
Intake performance is one of the most important factors relating with the forebody-inlet design for air-breathing hypersonic vehicles. The intake performance will be altered due to hypersonic flow field change by the thermal deformation of forebody and inlet under long-endurance aerothermal loads, resulting in endangering flight safety. Based on the in-house coupled analysis platform for thermal environment and structure response, the fluid/thermal/structural coupling simulation for a typical forebody-inlet geometrical model was performed to investigate the effect of ramp and cowl thermal deformation on inlet shock wave series and intake performance. The results show that under the effect of aerothermoelasticity during long cruise, inlet deviates from the design conditions, and the shock waves shift and oscillate. This further leads to an increase in inlet mass flow coefficient, a decrease in total pressure recovery coefficient and an increase in static pressure ratio. The influence of intake performance under thermal deformation is worthy to be considered in the design of air-breathing hypersonic vehicles.